2006
DOI: 10.4049/jimmunol.177.8.5377
|View full text |Cite
|
Sign up to set email alerts
|

Two-Sided Roles of IL-27: Induction of Th1 Differentiation on Naive CD4+ T Cells versus Suppression of Proinflammatory Cytokine Production Including IL-23-Induced IL-17 on Activated CD4+ T Cells Partially Through STAT3-Dependent Mechanism

Abstract: Recent lines of evidence have demonstrated that IL-27, a newly identified IL-12-related cytokine, has two apparently conflicting roles in immune responses: one as an initiator of Th1 responses and the other as an attenuator of inflammatory cytokine production. Although the IL-27-mediated Th1 initiation mechanism has been elucidated, little is known about the molecular basis for the suppression of cytokine production. In the present study, we demonstrated that IL-27 suppressed the production of various proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
193
3
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 50 publications
21
193
3
4
Order By: Relevance
“…However, there is a recent study demonstrating that the suppressive effect of IL-27 in STAT3-deficient CD4 ϩ T cells is significantly lower than that in wild-type cohorts, and it concluded that the preferential activation of STAT3 in fully activated CD4 ϩ T cells plays an important role in the cytokine suppression by IL-27 (22). The results of this article appear to be consistent with the mechanism by which IL-10 induces anti-inflammatory responses through STAT3 in macrophages (21,49,50), but not with the present results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a recent study demonstrating that the suppressive effect of IL-27 in STAT3-deficient CD4 ϩ T cells is significantly lower than that in wild-type cohorts, and it concluded that the preferential activation of STAT3 in fully activated CD4 ϩ T cells plays an important role in the cytokine suppression by IL-27 (22). The results of this article appear to be consistent with the mechanism by which IL-10 induces anti-inflammatory responses through STAT3 in macrophages (21,49,50), but not with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…These results may presumably imply a role of STAT3 in IL-27-induced cell proliferation. In addition, because one of the IL-27R subunits is the common gp130, and IL-27 can activate STAT3 and induce the suppressor of cytokine signaling (SOCS)-3 expression (19,20), the possibility that IL-27 induces anti-inflammatory response in a mechanism similar to the IL-10-induced STAT3-mediated one was discussed previously (21,22). However, the precise role of STAT3 and its molecular mechanism in not only IL-27-induced cell proliferation but also IL-27-induced anti-inflammatory response remain to be elucidated.…”
Section: Stat3 Is Indispensable To Il-27-mediated Cell Proliferation mentioning
confidence: 99%
“…Several papers described the IL-12-independent induction of Th1 cells via IL-27-dependent activation of STAT-1 and T-bet [37]. IL-27 is also involved in the inhibition of Th17 development [38], which could explain the absence of IL-17 increase, although DCs matured with PL-MSCs produced more IL-23 [39]. In line with these results, we showed recently that IL-27 is expressed highly in symptomatic PLs, and that the exogenous IL-27 can stimulate Th1 and down-regulate Th17 cytokines' production by the PL-inflammatory cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that despite eliciting strong IL-10 induction in the primary stimulation of T cells, IL-27 by itself was not sufficient to promote the formation of a stable, IL-10 producing Th cell lineage (not shown). Indeed, others have demonstrated that IL-27 suppresses IL-10 production upon repeated stimulation, while it caused induction of IL-10 production in FACS-purified naive T cells (13).…”
Section: Il-27 Induces Il-10 Expression By Cd4 ϩ and Cd8 ϩ T Cellsmentioning
confidence: 99%